Rolling adhesion of schizont stage Malaria-infected red blood cells in shear flow - Dasanna, Anil Kumar; Lansche, Christine; Lanzer, Michael; Schwarz, Ulrich S. (Biophysical journal, 2017)
To avoid clearance by the spleen, red blood cells infected with the human malaria parasite Plasmodium falciparum (iRBCs) adhere to the vascular endothelium through adhesive protrusions called “knobs” that the parasite induces on the surface of the host cell. However, the detailed relation between the developing knob structure and the resulting movement in shear flow is not known. Using flow chamber experiments on endothelial monolayers and tracking of the parasite inside the infected host cell, we find that trophozoites (intermediate-stage iRBCs) tend to flip due to their biconcave shape, whereas schizonts (late-stage iRBCs) tend to roll due to their almost spherical shape. We then use adhesive dynamics simulations for spherical cells to predict the effects of knob density and receptor multiplicity per knob on rolling adhesion of schizonts. We find that rolling adhesion requires a homogeneous coverage of the cell surface by knobs and that rolling adhesion becomes more stable and slower for higher knob density. Our experimental data suggest that schizonts are at the border between transient and stable rolling adhesion. They also allow us to establish an estimate for the molecular parameters for schizont adhesion to the vascular endothelium and to predict bond dynamics in the contact region.